Pemanfaatan Larva Black Soldier Fly (Hermatia illucens) sebagai Penanggulangan Sampah Organik melalui Budidaya Magot - Fifi Fata'tiatul Hidayah; Destya Nurfrida Rahayu; Candra Budiman (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Tuwel Village is the village with the most population and automatically the amount of organic waste donated by the community also increases. Organic waste is exacerbated by the absence of a Temporary Disposal Site in the village. Environmental pollution that occurs in the form of an unpleasant odor arises as a result of spoilage of organic material from waste. Maggot is one of the potential organisms that can break down organic waste. The village community does not have knowledge about maggot cultivation which can provide benefits. The purpose of this program is to inform the public about organic waste management and increase the economic value of the community through waste management activities. The method used is the socialization and designation of maggot metamorphosis. Both activities were carried out on two different days with 3 different places. The result of this program is that the community understands the life cycle of maggot, the procedures for cultivating maggot, the benefits in cultivating maggot, a type of organic waste that can be processed by maggot. Organic waste is useful as a medium for maggot cultivation. During the activity, participants actively listened and asked questions in the question and answer session. Keywords: cultivation, maggot, organic waste, socialization